Ball-milling assisted fabrication of hierarchical Na4Ti5O12/Na2Ti6O13 for enhanced tetracyclines photodegradation - Li, Ping; Lv, Ying; Chen, Xuelian; Li, Xiangjuan; Xie, Jianfeng; Zheng, Jialu (Colloids and surfaces. A, Physicochemical and engineering aspects, 2022)
Successful techniques for the evacuation of antibiotics are of colossal importance and profoundly attractive for satisfying the squeezing need for ecological remediation. Sodium titanates (NTO) as alluring inorganic materials for different applications because of their extraordinary physicochemical properties and low-cost. In this work, we demonstrated the utilization of NTO as photocatalysts, which are acquired by means of a ball-milling assisted heat treatment approach. A regular organic dye, methylene orange (MO), was utilized to examine the photodegradation properties of NTOs. The as-orchestrated Na4Ti5O12/Na2Ti6O13 displayed the greatest mineralization of MO. Particularly, the Na4Ti5O12/Na2Ti6O13 photocatalyst was used to degrade three tetracyclines with the degradation efficiency of tetracycline (TC), chlortetracycline (CTC) and oxytetracycline (OTC) were 80.78 %, 90.39 % and 75.60 %, respectively. In-depth experimental and DFT investigation proved that the relatively narrow bandgap of Na4Ti5O12 induced effective transformation of photo-excited electrons, thus reduced combination of carriers. Moreover, the heterojunction of Na4Ti5O12/Na2Ti6O13 induced the generation of active radicals and transport of carriers are proposed as advantages for the mineralization of three antibiotics. [Display omitted] •Sodium titanates materials were prepared by ball-milling assisted calcination process.•Systematic comparison of different calcination temperatures on phase composition and photocatalytic performance.•Na4Ti5O12/Na2Ti6O13 was formed by calcined at 700 °C has the highest photocatalytic activity.•Mineralization mechanism of three tetracycline antibiotics were explored.